Trolling brands and consumers in the era of social media: The trolling phenomenon in business contexts - Okan, M. (IGI Global, 2024)
The author of this chapter reviews the literature on the trolling behaviors of online users and proposes a conceptual framework to elucidate the role of the trolling phenomenon in marketing-related contexts. At first, this chapter presents a comprehensive multidisciplinary investigation that builds upon previous conceptualizations of trolling behaviors. Based on this investigation, the author summarizes the fundamental and distinctive characteristics of trolling acts. Then, this chapter suggests a conceptual framework that explains mechanisms predicting these behaviors and potential outcomes. Finally, this chapter provides a detailed overview of the antecedents and consequences of trolling behaviors by consumers against brands and other consumers in online contexts. © 2024, IGI Global. All rights reserved.